Importance of the collection 2020 federal income tax about the rent for the mexican financial system - Medina, Horacio Puentes (2020)
Objective: To analyze the economic and financial importance that the Income Tax (ISR) represents for the Mexican financial system and for the international GDP of the World Bank, using the quantitative procedures through the analysis of economic, accounting and financial factors. Method: In this research, the inductive and quantitative methods will be applied, and then the analytical and finally the deductive methods will be used. Results: The financial participation that will be received by the Ministry of Finance and Public Credit in the collection of the Income Tax "ISR" in 2020, will be approximately $1,852,852,300,000.00 MXN and that in U.S. dollars represents the amount of 84,220,559,091.00 US$, (eighty-four thousand two hundred and twenty million five hundred and fifty-nine thousand ninety-one dollars, the problem that currently faces the Financial System of the Mexican Government in the decrease in the collection of taxes in 2020. Conclusions: The differences in real amounts of the Revenue Laws were determined, which allowed us to see the effective situation of the income that will be recovered in 2020 from the ISR, and that will be reduced to: 1 667 567 070 000.00 (one billion six hundred and sixty seven thousand five hundred and sixty seven million, seventy thousand pesos 00/100 M.N.), and in U.S. dollars will be 75 798 503 182.00 US$, (seventy-five thousand seven hundred and ninety-eight million five hundred and three thousand one hundred and eighty-two dollars, with a drop of 10% of the gross domestic product in the economy of the Mexican State.